2017
DOI: 10.1177/1469066717732286
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of air-, moisture- and solvent-sensitive chemical compounds by mass spectrometry using an inert atmospheric pressure solids analysis probe

Abstract: A novel method has been developed that enables chemical compounds to be transferred from an inert atmosphere glove box and into the atmospheric pressure ion source of a mass spectrometer whilst retaining a controlled chemical environment. This innovative method is simple and cheap to implement on some commercially available mass spectrometers. We have termed this approach inert atmospheric pressure solids analysis probe ( iASAP) and demonstrate the benefit of this methodology for two air-/moisture-sensitive ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…36 The ASAP source has been used in many applications for both targeted analysis [37][38][39] and untargeted analysis. [40][41][42] Unlike other techniques that require uncontrolled multi sophisticated preparation steps or modified setups, 43,44 in our new simple approach, referred to as paraffin-inert ASAP (piASAP), 45 a capillary tube containing air-sensitive compounds (liquid or solid) is sealed with paraffin plug under inert atmosphere condition. The sample is thus protected in a sealed glass capillary under inert atmosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 The ASAP source has been used in many applications for both targeted analysis [37][38][39] and untargeted analysis. [40][41][42] Unlike other techniques that require uncontrolled multi sophisticated preparation steps or modified setups, 43,44 in our new simple approach, referred to as paraffin-inert ASAP (piASAP), 45 a capillary tube containing air-sensitive compounds (liquid or solid) is sealed with paraffin plug under inert atmosphere condition. The sample is thus protected in a sealed glass capillary under inert atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…This latter ionization mode has been established by McEwen in 2005 and allows analysis of pure or solution samples directly deposited on a glass tip, where the analyte is desorbed by a hot nitrogen flux and ionized by nitrogen plasma generated by corona discharge . The ASAP source has been used in many applications for both targeted analysis and untargeted analysis. Unlike other techniques that require uncontrolled multisophisticated preparation steps or modified setups, , in our new simple approach, referred to as paraffin-inert ASAP (piASAP), a capillary tube containing air-sensitive compounds (liquid or solid) is sealed with a paraffin plug under inert atmospheric condition. The sample is thus protected in a sealed glass capillary under inert atmosphere, and it can be transported and carried away as long as the paraffin plug is intact.…”
Section: Resultsmentioning
confidence: 99%
“…Mosely et al reported using a melting point tube (MPT) in which they loaded the air-sensitive sample for analysis in a glovebox. 82 The MPT was enclosed in plasticine and then sealed with a flame after taking it out of the glovebox. The MPT is heated and stretched (2-3 cm away from the sample) and carefully broken to give a shorter length MPT.…”
Section: Atmospheric Solids Analysis Probementioning
confidence: 99%
“…A tungsten cluster was only observed by iASAP, and only decomposition products were observed with the ASAP technique. 82 In 2020, Naim et al reported the analysis of air-sensitive solids and liquids by paraffin-inert atmospheric solids analysis probe 83 This method allows the study of air-sensitive compounds using a glass capillary filled with a sample and then sealed by a paraffin plug to maintain the inert sample until the ionization process, as seen in Figure 18. The sample can then be taken out of the glovebox and inserted in the ASAP probe as long as the paraffin is intact.…”
Section: Atmospheric Solids Analysis Probementioning
confidence: 99%
“…16 More recently, a related approach, “Paraffin-Inert ASAP” was been reported by Afonso, Giusti, and co-workers, which involves sealing a capillary loaded with sample with paraffin in a glovebox to protect the sample during transport to the machine. 17 Building on our prior work around developing methods for the analysis of air-/moisture-sensitive samples via ASAP MS, 18 we describe herein the design and use of a cheap, simple, and reusable glass probe delivery sample system whose configuration can be very easily modified to fit any vertically loading ASAP mass spectrometer providing an alternative methodology for analysis of environmentally sensitive solid and liquid materials. This approach is straightforward, readily applicable, and requires no alterations to the Waters mass spectrometry instruments used in this study and can easily be modified for use with other instruments.…”
Section: Introductionmentioning
confidence: 99%